A Study on Post Purchase Behaviour with Special Reference to Mahindra Two Wheelers - Anitha, R.; Kanimozhi, V. (Indian Journal of Marketing, 2013)
The two-wheeler market in India is the biggest contributor to the automobile industry, with a size of â‚¹100,000 million. Today’s customers are becoming harder to please. They are smarter, more price conscious, more demanding, less forgiving, and collect information about many more competitors with equal or better offers. The interaction between consumer expectations and actual product performance produces either satisfaction or dissatisfaction. At the higher levels of satisfaction, customers are likely to re-purchase and even speak well of the company and its products. The study aimed to assess expectations, perceptions, and post purchase behaviour of Mahindra scooter customers, which will enable both the manufacturer and the distributors to know about the customers’ expectations, perceptions, and post purchase behaviour, that in turn helps to reduce the post purchase dissonance and aids in enhancing customer satisfaction.